(untitled) - Westlake, Michael John (Rome, 2005)
One of the main objectives of the Agreement on Agriculture (AoA) negotiated under the Uruguay Round is to improve the access of developing countries to foreign markets. Constraints in the domestic supply chains of many countries, along with weak marketing support and trade facilitation services, have prevented them, however, from exploiting the opportunities provided by the AoA and by other agreements to improve market access. The aim of this guide is to inform policy analysts on issues that should be considered while developing policies and measures to break the main processing and marketing constraints that prevent their countries from fully exploiting their agrifood export potential.
Keywords: Agriculture,Nông nghiệp; Economic aspects,Khía cạnh kinh tế